The trend of 3D Printing in higher TVET skill level - Kumaran, Kadirgama; Wan Sharuzi, Wan Harun (2020)
Additive Manufacturing is a recent trend in production processes owing to its many benefits around the globe. It can be defined as the process of producing parts through the deposition of material in a layer-by-layer technique. It has been the most searchable and research topic by various researchers since the year 2000 up to now. According to Frost and Sullivan the value of additive manufacturing is expected to grow at a rate of 15% from US$5.31 billion in 2015 to US$21.50 billion in 2025. The industries that are going to contribute 51% by 2025 are aerospace, automotive, and medical industries.